Drifting along in the open-ocean: The associative behaviour of oceanic triggerfish and rainbow runner with floating objects. (October 2020) - Forget, Fabien; Cowley, Paul D.; Capello, Manuela; Filmalter, John D.; Dagorn, Laurent
Abstract: Multispecies aggregations at floating objects are a common feature throughout the world's tropical and subtropical oceans. The evolutionary benefits driving this associative behaviour of pelagic fish remains unclear and information on the associative behaviour of non-tuna species remains scarce. This study investigated the associative behaviour of oceanic triggerfish ( Canthidermis maculata ) and rainbow runner ( Elagatis bipinnulata ), two major bycatch species in the tropical tuna purse seine fishery, at floating objects in the western Indian Ocean. A total of 24 rainbow runner and 46 oceanic triggerfish were tagged with acoustic transmitters at nine drifting FADs equipped with satellite linked receivers. Both species remained associated with the same floating object for extended periods; Kaplan-Meier survival estimates (considering the censored residence time due to equipment failure and fishing) suggested that mean residence time by rainbow runner and oceanic triggerfish was of 94 and 65 days, respectively. During daytime, the two species increased their home range as they typically performed short excursions (<2 h) away from the floating objects. Rainbow runner performed more excursions per unit time than oceanic triggerfish; the mean excursion index was 0.86 (±0.8 SD) for oceanic triggerfish and 1.31 (±1.1 SD) for rainbow runner. Ambient light intensity appears to be the stimulus triggering the onset and end of the associative modes. The observed prolonged residency of these two major bycatch species suggests that they are more vulnerable to the tropical tuna purse seine gear than the targeted tuna species. Highlights: The associative behaviour of oceanic triggerfish ( Canthidermis maculata ) and rainbow runner ( Elagatis bipinnulata ) were investigated using acoustic telemetry satellite linked receivers at floating objects in the western Indian Ocean. Both species remained associated with the same floating object for extended periods with mean residency estimated at 94 days for rainbow runner and 65 days for oceanic triggerfish. A strong diel pattern was observed for both species with short excursions (<2 h) away from the floating objects observed during the day. Ambient light intensity appears to be the stimulus triggering the onset and end of the associative modes. The prolonged residency of these two species suggests that they are more vulnerable at FADs than the targeted tuna species.